Combinatorial Properties of the Difference Set With Respect to CPHMs of Row Sum 0 and 2 - Manjhi, Pankaj Kumar; Kumar, Jitendra (Communications in Mathematics and Applications, 2025)
This article investigates the combinatorial properties of difference sets within the cyclic group \(\mathbb{Z}_n\), specifically in the context of Circulant Partial Hadamard Matrices (CPHMs). We examine the structural characteristics and establish relationships between difference sets associated with \(2\text{-}H(m × n)\) and \(0\text{-}H(m × n)\) matrices. Our results provide insights into the interplay between these matrix classes and their corresponding difference sets, contributing to the broader understanding of their applications in combinatorial design theory.